Systematisation of Scientific approaches to the definition of capital as an Economic and accounting category - M. V. Protasov (Учёт. Анализ. Аудит, 2023)
Capital is a complex definition and differences in its interpretations lead to ambiguous perception of information by specialists from different scientific fields, incl. accounting. In the course of the work, it was revealed that the views of representatives of economic schools on the concept of “capital” became more complicated due to both positive perception and criticism of previous scientific works, depending on the current economic conditions. This allowed the author to present his own opinion on the impact of different approaches to the interpretation of this term on the development of accounting methods, its evolution in accounting and balance sheet theories, which was the purpose of this study. The definition of “capital” in accounting has come a long way of development, starting from the digraphic stage, characterized by the appearance of a double entry. Since this work on the study of the development of the concept of Capital was carried out in the context of the classification of accounts, taking into consideration the economic and legal interpretation of business transactions; its result was the author’s vision of the evolution of accounts and the place of Capital in this system. The scientific novelty of this work lies in the fact that, based on the historical-logical approach and the method of system-chronological analysis, the development of the definition of Capital in accounting and balance theories has been studied with the justification of its special function — an indicator of the increase or depletion of resources that generate economic benefits and profits remaining at the disposal of the owners of the organization. The theoretical significance of the work lies in the generalization of existing knowledge and the improvement of the conceptual apparatus of the definition of Capital. The results of this work can be used to improve individual financial reporting taxonomies. In the process of research, such methods as grouping, system-chronological analysis, comparison, generalization were used.